2022
DOI: 10.1080/21655979.2022.2048994
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 10 alleviates doxorubicin-induced cardiac injury via signal transducer and activator of transcription 3 signaling pathway

Abstract: Doxorubicin (DOX) has limited antitumor applications owing to its association with life-threatening cardiac injury. Oxidative damage and cardiac apoptosis are crucial in DOX-induced cardiac injury. Bone morphogenetic protein 10 (BMP10) is predominantly distributed in the heart and acts as a cardioprotective factor that preserves cardiac function. However, the role of BMP10 in DOX-induced cardiac injury has not yet been explored. The current study aimed to examine the function and mechanism of action of BMP10 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Previously, BMP-2 was reported to alleviate DOX-induced cardiomyocyte injury in vitro (Izumi et al, 2006). Recently, Peng et al reported that DOX treatment decreased BMP-10 expression in mouse hearts and that cardiac-specific BMP-10 inhibition aggravated oxidative stress and apoptosis and worsened cardiac function, whereas cardiac-specific BMP-10 overexpression and exogenous BMP-10 supplementation ameliorated DOX-induced cardiac dysfunction by activating STAT3 signaling (An et al, 2022).…”
Section: The Bmp Family and Aortic Dissection (Ad)mentioning
confidence: 99%
“…Previously, BMP-2 was reported to alleviate DOX-induced cardiomyocyte injury in vitro (Izumi et al, 2006). Recently, Peng et al reported that DOX treatment decreased BMP-10 expression in mouse hearts and that cardiac-specific BMP-10 inhibition aggravated oxidative stress and apoptosis and worsened cardiac function, whereas cardiac-specific BMP-10 overexpression and exogenous BMP-10 supplementation ameliorated DOX-induced cardiac dysfunction by activating STAT3 signaling (An et al, 2022).…”
Section: The Bmp Family and Aortic Dissection (Ad)mentioning
confidence: 99%
“…To establish acute cardiotoxicity, male mice with 8-10-week-old were injected with DOX (15 mg/kg, i.p.) once, and then sacrificed by cervical dislocation 8 days post-DOX injury [ 22 ]. To clarify the role of AMPK in LUZP1-mediated protections against DOX-induced cardiotoxicity, LUZP1 cTG mice were mated with Ampkα2 knockout (KO) mice to generate cardiac-specific Luzp1 transgenic mice with Ampkα2 deficiency, and global Ampkα2 KO mice has been used previously [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…To clarify the role of AMPK in LUZP1-mediated protections against DOX-induced cardiotoxicity, LUZP1 cTG mice were mated with Ampkα2 knockout (KO) mice to generate cardiac-specific Luzp1 transgenic mice with Ampkα2 deficiency, and global Ampkα2 KO mice has been used previously [ 14 ]. To specifically silence PPP1CA/B in the myocardium, LUZP1 cKO mice were injected from tail vein with AAV9 (1 × 10 11 VG particles/mouse) carrying pan PP1 shRNA (sh PP1 , #sc-43533; Santa Cruz, Dallas, Texas, USA) under a cTnT promoter 4 weeks pre-DOX injury [ [22] , [23] , [24] ]. To investigate whether LUZP1 overexpression also conferred cardioprotective effects on DOX-induced chronic injury, LUZP1 cTG mice or the non-transgenic (NTG) controls were weekly injected with 5 mg/kg DOX (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DOX exposure decreased the initial level of BMP10 in the heart, exogenous supplementation may ameliorate DOX‐induced systolic dysfunction. DOX cardiotoxicity decreased phosphorylation of signal transducer and activator of transcription 3 (STAT3), and exogenous BMP10 reversed the defective STAT3 via a noncanonical pathway 38 . Hence, it is evident that BMP10 has the capacity to elicit cardiomyocyte value‐added and thereby counteract cardiac damage, both for cell death due to myocardial ischemia and cardiac injury induced by drugs, and that this capacity might be achieved via the STAT3 pathway.…”
Section: Bmp10 In Cardiovascular Diseasementioning
confidence: 99%